A gestão dos riscos ocupacionais na Universidade Federal de Uberlândia - Martinez, Fernando Rocha (2024)
This research aimed to analyze the management of occupational risks at the Federal University of Uberlândia (UFU). To achieve this, the study investigated the risk factors to which employees in various university sectors are exposed, their perception of the analysis and control of these risks, and the involvement of management in this matter. Participants in this study included employees from eleven academic units working in areas with a higher probability of risks at the Umuarama campus, where a larger percentage of employees receive hazardous duty pay due to exposure to occupational risks. The research is characterized as an exploratory multimethod study, utilizing quantitative and descriptive approaches (structured closed questionnaire) as well as qualitative methods (interviews). Initially, questionnaires were sent to 743 employees, resulting in 153 responses. However, only 139 met the inclusion criteria for this study. Additionally, semistructured interviews were conducted with eight managers who agreed to participate in the research. The findings indicated that risks are constant in work activities, with chemicals and biological agents being the most prevalent. It was observed that the majority of employees recognize these agents as potential threats to their health and safety, with a significant likelihood of causing illness and accidents, as nearly 60% admitted to experiencing consequences from these risks. A gap in communication to managers regarding the reporting of these accidents was noted, along with the absence of a formal system for recording such incidents in the analyzed units. Both groups (employees and managers) agree that risks could be reduced with improvements in infrastructure and the modernization of equipment. However, limitations such as a lack of financial resources and bureaucratic issues hinder the implementation of these measures. The risk analysis revealed a lack of support from the Occupational Safety Sector for inspections, training, and occupational safety advice. Regarding risk control, nearly half of the employees are dissatisfied with the physical structure, machines, and equipment or furniture in the workplace, although the majority agrees on the need for the provision of personal protective equipment. Concerning management involvement, worrisome data were found related to the disclosure of information about risks and the scarcity of capacity-building/training. However, most employees have a positive view of managers regarding their interest in safety, working conditions, and allocated resources. On the other hand, employees did not recognize recent investments made by the university in this regard. The absence of a structured Risk Management Program (RMP) in academic units became evident, although managers understand the potential benefits of adopting an RMP. It is hoped that our results will inspire initiatives at UFU to seek significant improvements in occupational safety and the establishment of a concrete occupational safety policy, possibly through the implementation of an RMP, contributing to the promotion of better working conditions, health, and well-being for employees and supporting managers in their essential role.